Impact of latent toxoplasmosis on pneumonic and non-pneumonic COVID-19 patients with estimation of relevant oxidative stress biomarkers - Hamdy, Doaa A; Eid, Ragaey A; Abdel-Tawab, Heba; El-Badry, Mohamed A; Abdallah, Abdelrahman M; El Wahab, Wegdan M Abd (Folia parasitologica, 2024)
Susceptibility to COVID-19, the most devastating global pandemic, appears to vary widely across different population groups. Exposure to toxoplasmosis has been proposed as a theory to explain the diversity of these populations. The aim of the present study was to investigate the possible association between latent toxoplasmosis and COVID-19 and its probable correlation with markers of oxidative stress, C-reactive protein (CRP) and ferritin. In a case-control study, blood samples were collected from 91 confirmed (48 non-pneumonic; NP, and 43 pneumonic; P) COVID-19 patients and 45 healthy controls. All participants were tested for IgG anti-Toxoplasma gondii antibodies and oxidative stress markers (nitric oxide [NO], superoxide dismutase [SOD] and reduced glutathione [GSH]), and CRP and serum ferritin levels were determined. In COVID-19 patients, IgG anti-T. gondii antibodies were found in 54% compared to 7% in the control group, with the difference being statistically significant (P ˂ 0.001). However, no significant correlation was found between the severity of COVID-19 and latent T. gondii infection. Latent toxoplasmosis had a strong influence on the risk of COVID-19. NO and SOD levels were significantly increased in COVID-19 patients, while GSH levels decreased significantly in them compared to control subjects (P ˂ 0.001 for both values). CRP and ferritin levels were also significantly elevated in P COVID-19 patients infected with toxoplasmosis. This is the first study to look at the importance of oxidative stress indicators in co-infection between COVID-19 and T. gondii. The high prevalence of latent toxoplasmosis in COVID-19 suggests that T. gondii infection can be considered a strong indicator of the high risk of COVID-19.
Keywords: Nitric Oxide; protilátky protozoální; oxidační stres; Immunoglobulin G; Ferritins; biologické markery; Seroepidemiologic Studies; Risk Factors; séroepidemiologické studie; Biomarkers; antioxidants; Toxoplasma gondii; Antibodies, Protozoan; imunoglobulin G; toxoplazmóza; oxid dusnatý; Case-Control Studies; SARS-CoV-2; ferritin.; lidé; Toxoplasmosis; C-reactive protein; studie případů a kontrol; Humans; rizikové faktory; ferritiny; Superoxide Dismutase; Oxidative Stress; superoxiddismutasa; COVID-19